Spontaneous symmetry breaking of Kerr solitons in Fabry Perot Resonators - Hill, Lewis; Hirmer, Eva Maria; Campbell, Graeme; Ghosh, Alekhya; Bi, Toby; Oppo, Gian Luca; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics, CLEO 2023, 2023)
Symmetry breaking of vector temporal cavity solitons in Fabry-Perot resonators is presented. This work can improve the generation of frequency combs through its control of the number of cavity solitons in a round trip.
CRIS-Team Scopus Importer:2023-11-24